Penguatan Literasi Quran Pada Anak Usia Dini Di TPQ Syuhadak Desa Lopang Kecamatan Lamongan, Kabupaten Lamongan - Muhammad Dzikri Abadi; Aranta Prista Dilasari; Ita Shobakhul Lama’ah; Fitrotul Azizah; Nurus Sabillah (Universitas Muhammadiyah Manado, 2021)
The purpose of Community Service is to improve the quality of early childhood in reading the Qur'an in Lopang Village, Kembangbahu Regency and find out what obstacles are experienced in learning the Quran at TPQ Syuhadak. The method used by preparing material that will later be applied as an interactive learning method. So that it is easy to understand and remember by children. From this dedication, it can also be known what obstacles and obstacles exist in TPQ Shuhadak both internally and externally in an effort to improve the quality of reading the Quran in early childhood.